Linfonodo sentinela axilar e sua correlação com fatores prognósticos em cães com neoplasias mamárias - Aline Gomes de Castro (2018)
Mammary tumors have major importance in pet clinic and are the most common neoplasms in bitches. Sentinel lymph node is defined as the first lymph node of a regional lymphatic chain to drain lymph from the neoplastic site. The possibility of identification of sentinel axillary lymph node with patent blue dye has aided in the determination of regional metastasis, defining prognosis, survival and adjuvant therapies necessary. The objective of this study was to evaluate the axillary lymph node of dogs with breast neoplasm submitted to mastectomy, to evaluate the method of identification by the patent blue technique and to correlate the presence of lymph node metastasis with some prognostic factors of malignancy and histological types of neoplasms. Fifty dogs (49 females and one male) from the clinical-surgical routine of the UFMG Veterinary Hospital from April/2015 to May/2017 were evaluated with mammary tumors located on the axillary lymph drainage site, clinical stage II or III, and non-palpable axillary lymph node (LA). All animals were submitted to mastectomy and 2.5% patent blue application for LA identification. In 38 animals (76%) it was possible to identify the stained sentinel lymph node, in other cases the lymph node was not identified. The probability of finding LA did not differ when correlated to tumor size and animal weight and no animal showed a reaction to the dye. Of the 38 animals with LA histologically assessed only 14 (36.84%) had metastasis. There was no significant difference (p> 0.05) between the likelihood of finding metastasis and the location of the tumor, the presence of adhesion and the histological type of the neoplasm. However, the probability of finding metastasis was significant (p <0.05) for the variables tumor size / clinical staging, presence of ulceration and necrosis. It was concluded that the use of 2.5% blue patent was safe in dogs and contributed to the identification of LA in 76% of the cases studied. Animals with larger tumors (clinical stage III) and / or with ulcerated and / or necrotic tumors had a higher occurrence of metastasis in LA suggesting that patients with these characteristics should undergo mastectomy with LA excision for correct staging.